ANALISIS VIDEO KEJADIAN FISIKA DENGAN SOFTWARE TRACKER SEBAGAI RANCANGAN BAHAN AJAR MOMENTUM DAN IMPULS UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS SISWA SMA KELAS X - Lukman Fadholi; Alex Harijanto; Albertus Djoko Lesmono (FKIP Universitas Jember, 2018)
The purpose of this research was to analyze video of physics phenomenon on matter of momentum-impuls by using tracker software and then used as design of teaching material of momentum-impuls in increasing student critical thinking skills of senior high school at class X. This research type was research of descriptive analysis. The result of video analysis of physics phenomenon with tracker software prove there were 3 types of collision that were elastic collision, unelastic collision, and perfectly unelastic collision based on conservation of momentum, conservation of kinetic energy, and magnitude of restitution coefficients value. The magnitude of impuls equal to . The design of teaching material was design of student worksheets on momentum-impuls material to improve students' critical thinking skills consisting of titles, basic competencies, study guides, learning objectives, matter, assignments, and questions.Key words: video analyze, critical thinking skill, momentum and impuls, software tracker, teaching material